User P-Q Diagram as a Part of a Synchronous Generator Monitoring System - Vrazic, M.; Viskovic, A.; Hanic, Z. (Elektronika ir Elektrotechnika, 2014)
This paper describes the implementation of the P-Q capability diagram into the existing monitoring system for the 247 MVA synchronous turbo generator installed in a thermal power plant. The paper also addresses features, characteristics and uniqueness of the existing monitoring system as well as the modeling considerations required for the development of a P-Q diagram. This enables better insight into the operational limits which ensures better utilization of the synchronous generator. The proposed approach and methodology can be used for the implementation of the user real-time P-Q diagram whose limits change dynamically in accordance with operating conditions when the generator operates on the grid. DOI: http://dx.doi.org/10.5755/j01.eee.20.4.5333